Clinical significance of cachexia index in patients with hepatocellular carcinoma after hepatic resection. (December 2022) - Akaoka, Munetoshi; Haruki, Koichiro; Taniai, Tomohiko; Yanagaki, Mitsuru; Igarashi, Yosuke; Furukawa, Kenei; Onda, Shinji; Tsunematsu, Masashi; Shirai, Yoshihiro; Okui, Norimitsu; Gocho, Takeshi; Ikegami, Toru
Abstract: Background: Cancer cachexia has been associated with unfavorable outcomes in several malignancies. The cachexia index (CXI), which consists of skeletal muscle, inflammation, and nutritional status, has been proposed as a novel biomarker of cachexia. Therefore, we here investigated prognostic value of the CXI in patients with hepatocellular carcinoma (HCC) after hepatic resection. Methods: The study comprised 213 patients who had undergone primary hepatic resection for HCC between 2008 and 2018. First, the skeletal muscle index (SMI) was calculated as the area of the psoas muscle at the third lumbar vertebra/(the height) 2 . The CXI was then calculated by the following formula: SMI x serum albumin level/neutrophil-to-lymphocyte ratio (NLR). We retrospectively investigated the relationship between the CXI and disease-free survival as well as overall survival. Results: In multivariate analyses, female ( p  < 0.01), hepatitis B surface antigen-positivity ( p  < 0.01), preoperative serum alpha-fetoprotein level ≥20 ng/mL ( p = 0.01), preoperative serum protein induced by vitamin K absence or antagonist-II level ≥200 mAU/mL ( p = 0.02), multiple tumors ( p  < 0.01), macrovascular invasion ( p = 0.04), type of resection ( p  < 0.01), and low CXI ( p = 0.03) were significant predictors of disease-free survival, while Child-Pugh grade B ( p < 0.01), poor tumor differentiation ( p = 0.05), multiple tumors ( p = 0.01), macrovascular invasion ( p = 0.04), NLR ( p = 0.04), and low CXI ( p  < 0.01) were significant predictors of overall survival. In the subgroup analysis of advanced T stage, the CXI was associated with both disease-free ( p  < 0.01) and overall survival ( p  = 0.06). Conclusions: The CXI can be a prognostic indicator in patients with HCC after hepatic resection, suggesting the importance of comprehensive biomarker which includes skeletal muscle, inflammation, and nutritional status. Highlights: Cancer cachexia has been associated with poor survival in hepatocellular carcinoma. The cachexia index, which consists of skeletal muscle, inflammation, and nutritional status, can be useful for the assessment of cancer cachexia. The cachexia index may be a prognostic indicator in patients with hepatocellular carcinoma.